Imported occupational lead poisoning: report of four cases / Saturnismo d’importazione: descrizione di quattro casi - Petracca, Matteo; Scafa, Fabrizio; Boeri, Riccardo; Flachi, Daniela; Candura, Stefano Massimo (La Medicina del Lavoro, 2013)
Summary Background: In most industrialized countries, occupational lead poisoning has become increasingly rare, however this metal remains a serious health hazard in the rest of the world. Report of cases: We observed four male patients (aged 35 ÷ 54 years) who had suffered recurrent abdominal pain due to recent lead exposure (for 7 to 13 months) in two Chinese battery recycling plants. On their return to Italy, three of them presented normocytic, normochromic anaemia. The diagnosis was confirmed by high lead levels in the blood and urine, decreased erythrocyte δ-aminolevulinic acid dehydratase (ALA-D), raised erythrocyte zinc protoporphyrin (ZP), and elevated urinary excretion of δ-aminolevulinic acid (ALA-U) and porphyrins. Chelation with EDTA resulted in increased urinary lead excretion, improvement of the clinical picture, decreased ZP, and progressive normalization of the other lead biomarkers (Pb-B, ALA-D, ALA-U, urinary porphyrins). Conclusions: Temporary work in developing countries may result in imported lead poisoning. Differential diagnosis of this unusual condition requires careful medical history collection and specific toxicological analysis. Preventive measures for workers going abroad are needed. Riassunto «Saturnismo d’importazione: descrizione di quattro casi». Introduzione: Nei paesi maggiormente industrializzati, l’intossicazione professionale da piombo è ormai di rara osservazione. Questo metallo rimane tuttavia un serio rischio per la salute nel resto del mondo. Descrizione dei casi: Quattro pazienti maschi (età: 35 ÷ 54 anni) sono giunti all’osservazione dopo avere sofferto di dolore addominale ricorrente causato da recente esposizione al piombo (durata: 7 ÷ 13 mesi) in due impianti cinesi di riciclaggio batterie. Al rientro in Italia, tre di loro presentavano anemia normocitica normocromica. La diagnosi è stata confermata dal riscontro di: livelli elevati di piombo nel sangue e nelle urine, diminuzione dell’acido δ-aminolevulinico deidratasi (ALA-D) eritrocitaria, aumento della zinco protoporfirina (ZP) eritrocitaria, elevata escrezione urinaria di acido δ-aminolevulinico (ALA-U) e di porfirine. La chelazione con EDTA ha portato ad aumentata escrezione urinaria di piombo, miglioramento del quadro clinico, diminuzione della ZP e normalizzazione degli altri indicatori biologici (Pb-B, ALA-D, ALA-U, porfirine urinarie). Conclusioni: Periodi temporanei di lavoro in paesi in via di sviluppo possono essere causa di saturnismo d’importazione. La diagnosi differenziale di questa rara condizione richiede accurata anamnesi e analisi tossicologiche mirate. Sono necessarie adeguate misure preventive per i lavoratori che si recano all’estero.